The Lower Limit of Pitch Perception for Pure Tones and Low-Frequency Complex Sounds - Carlos JURADO; Marcelo LARREA; Brian C.J. MOORE (Archives of Acoustics)
The lower limit of pitch (LLP) perception was explored for pure tones, sinusoidally amplitude-modulated (SAM) tones with a carrier frequency of 125 Hz, and trains of 125-Hz tone pips, using an adaptive procedure to estimate the lowest repetition rate for which a tonal/humming quality was heard. The LLP was similar for the three stimulus types, averaging 19 Hz. There were marked individual differences, which were correlated to some extent across stimulus types. The pure-tone stimuli contained a single resolved harmonic, whereas the SAM tones and tone-pip trains contained only unresolved components, whose frequencies did not necessarily form a harmonic series. The similarity of the LLP across stimulus types suggests that the LLP is determined by the repetition period of the sound for pure tones, and the envelope repetition period for complex stimuli. The results are consistent with the idea that the LLP is determined by a periodicity analysis in the auditory system, and that the longest time interval between waveform or envelope peaks for which this analysis can be performed is approximately 53 ms.